Structure of quench condensed nH₂–N₂ binary alloys: isotope effect - Galtsov, N.N.; Prokhvatilov, A.I.; Strzhemechny, M.A. (Физика низких температур, 2007)
Structure of quench condensed nH₂–N₂ alloys was investigated by powder x-ray diffraction over a wide range of temperatures, compositions, and rates of deposition. The structure of the deposits is shown to depend on the condensation regime. Under mild regime, no solid nitrogen reflections from hydrogen-rich deposits were observed. When the temperature is increased to the hydrogen triple point, nitrogen lines appear at substantially larger angles compared to pure N₂, which suggests presence of dissolved hydrogen. The quantum nature of this hydrogen is suppressed in the nitrogen matrix. The samples grown in mild regime exhibit the highest apparent solubility (up to 25%) of hydrogen in solid N₂. When H₂ is substituted by D₂, the isotope effect consists in a wider range of mono-phase states based on the nitrogen cubic lattice, which can accommodate up to 70% of deuterium, if grown under mild regime.